Bell's palsy in pregnancy: underlying HELLP syndrome or pre-eclampsia?. (September 2013) - Pourrat, O; Neau, J-P; Pierre, F
Bell's palsy is not uncommon during pregnancy. An association with pre-eclampsia (PE) has been reported previously. Furthermore, it has even been suggested that Bell's palsy could be a predictor of PE. We report three cases illustrating various possible aspects of this association, one of them including the features of HELLP (haemolysis, elevated liver enzymes, and low platelets) syndrome.